Role of large MAF transcription factors in the mouse endocrine pancreas - ABDELLATIF, Ahmed M. (Exp Anim, 2015)
The members of the MAF family of transcription factors are homologs of v-Maf –the oncogenic component of the avian retrovirus AS42. The MAF family is subdivided into 2 groups, small and large MAFs. To elucidate the role of the large MAF transcription factors in the endocrine pancreas, we analyzed large MAF gene knockout mice. It has been shown that Mafa(−/−) mice develop phenotypes including abnormal islet structure soon after birth. This study revealed that Ins1 and Ins2 transcripts and the protein contents were significantly reduced in Mafa(−/−) mice at embryonic day 18.5. In addition, Mafa(−/−);Mafb(−/−) mice contained less than 10% of the insulin transcript and protein of those of wild-type mice, suggesting that Mafa and Mafb cooperate to maintain insulin levels at the embryonic stage. On the other hand, the number of insulin-positive cells in Mafa(−/−) mice was comparable to that of wild-type mice, and even under a Mafb-deficient background the number of insulin-positive cells was not decreased, suggesting that Mafb plays a dominant role in embryonic β-cell development. We also found that at 20 weeks of age Mafa(−/−);Mafb(+/−) mice showed a higher fasting blood glucose level than single Mafa(−/−) mice. In summary, our results indicate that Mafa is necessary for the maintenance of normal insulin levels even in embryos and that Mafb is important for the maintenance of fasting blood glucose levels in the Mafa-deficient background in adults.